DISCOURSE ANALYSIS OF BUSINESS MOTIVATORS' PUBLIC SPEAKING METHODS: A COMPARISON OF MIRZAKARIM NORBEKOV AND SIMON SINEK (European Journal of Interdisciplinary Research and Development, 2025)
Two well-known business motivators whose discourse techniques are studied in this article are Simon Sinek, an Anglo-American leadership theorist best known for his TED Talk, "How Great Leaders Inspire Action," and Mirzakarim Norbekov, a well-known Uzbek entrepreneur and motivational speaker. Using a discourse-analytic framework, the study examines rhetorical devices such as ethos, pathos, logos, metaphor, storytelling, performance style, and cross-cultural discourse patterns. The findings demonstrate how Sinek develops persuasion through the use of universal case studies, scientific metaphors, and organized logical reasoning. Additionally, he speaks in a calm, collected manner that is suitable for Western corporate audiences. On the other hand, Norbekov employs comedy, sarcasm, autobiographical narration, and traditional allusions in a vibrant and theatrical way that appeals to Russian and Uzbek audiences. The analysis highlights cultural differences - Sinek stands for low-context, linear, and individual-centered discourse traditions, while Norbekov represents high-context, relational, and community-centered discourse traditions.